Failure Mode and Effect Analysis of Buttterfly in UTHM Biodiesel Plant: Failure Mode and Effect Analysis - Borhanoddin, Amirul Iskandar; WAN ABDUL RAHMAN, WAN MOHD WARDI (Research Progress in Mechanical and Manufacturing Engineering, 2024)
This study presents a Failure Mode and Effect Analysis (FMEA) conducted on butterfly valves in the UTHM biodiesel plant. The objective of this research is to assess the risks associated with butterfly valves and develop targeted risk mitigation strategies to enhance safety, reliability, and performance in the plant. The literature review explores the existing knowledge on butterfly valve failures, FMEA methodologies, and previous studies conducted in the oil and gas industry. The methodology section outlines the research design, data collection procedures, and the FMEA process, including severity, occurrence, and detection assessments. The study aims to identify critical failure modes, assign risk priority numbers, and propose effective risk control measures. The expected results include a comprehensive understanding of failure modes specific to butterfly valves in the UTHM biodiesel plant, prioritized risk areas, and targeted risk mitigation strategies. The significance of this research lies in its potential to minimize failures, reduce downtime, optimize resources, and contribute to the existing knowledge in butterfly valve failure analysis. The findings of this study can be used to enhance the safety and reliability of butterfly valves in the UTHM biodiesel plant and potentially benefit other similar industrial applications.